Motivasi Belajar dan Konsentrasi Belajar Peserta Didik: Studi Korelasional pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMK - Putri Maharani Kay; Guntur Cahaya Kesuma; Uswatun Hasanah (WISE Pendidikan Indonesia, 2026)
Learning motivation and learning concentration are essential psychological factors influencing students’ engagement and academic achievement, particularly in Islamic Religious Education and Character Building subjects. However, preliminary observations at SMK Negeri 1 Kotabumi indicated that students demonstrated low learning motivation and concentration, reflected in limited classroom participation, low learning interest, monotonous teaching methods, and less interactive learning environments. Therefore, this study aimed to analyze the correlation between students’ learning motivation and learning concentration in Islamic Religious Education and Character-Building classes at SMK Negeri 1 Kotabumi. This study employed Self-Determination Theory (SDT) developed by Deci and Ryan as the grand theory to explain the relationship between intrinsic motivation and students’ psychological engagement during learning activities. A quantitative approach with a correlational ex-post facto design was applied. The population consisted of 419 eleventh-grade students, and a sample of 81 respondents was determined using the Slovin formula with a 10% margin of error through simple random sampling. The learning motivation variable was operationalized using Hamzah B. Uno’s theory, while learning concentration was measured using Slameto’s theory. Data were collected through questionnaires and analyzed using correlational statistical analysis. The findings revealed a positive and significant correlation between learning motivation and learning concentration, indicating that students with higher motivation tended to demonstrate better concentration during learning activities. The novelty of this study lies in examining the relationship between learning motivation and learning concentration, which remains underexplored in Islamic educational contexts, particularly among vocational high school students. This study is expected to contribute theoretically to Islamic educational psychology and practically to the development of more engaging and student-centered learning strategies.